Examining The Role Of Leader Mindfulness And Employee Moral Identity In Shaping Workplace Dynamics: A Study On Nurses’ Experience Of Leader Surface Acting And Incivility In Hospitals - Zulfiqar, Nawal; Ajmal, Dr. Muhammad; Islam, Azmat (Migration Letters, 2024)
The detrimental impacts of inadequate leadership on organizational efficiency and productivity have become increasingly conspicuous over time, undermining the overall performance of institutions. This research endeavors to delineate potential strategies to mitigate such adverse behaviors and safeguard the organizational milieu. Crucially, the mindfulness of leaders is instrumental in curtailing unethical conduct, while the moral identity of employees also serves as a deterrent to such phenomena. Theories of ego depletion and resource conservation furnish a theoretical foundation to elucidate these relationships. Employing a cross-sectional methodology, data were gleaned from nurses employed in private hospitals within Pakistan. The analysis of latent constructs was facilitated through confirmatory factor analysis (CFA), thereby estimating the measurement model. Subsequently, structural equation modeling (SEM), executed via AMOS V24 Software, was deployed to evaluate the hypothesized relationships. The findings indicate that abusive supervisory behavior acts as a mediating variable between leader surface acting and the emergence of workplace incivility. These insights advocate the implementation of initiatives centered on mindfulness and moral identity to foster a conducive and progressive organizational climate. Consequently, management in private healthcare settings is advised to scrutinize their behavior meticulously to preserve the institution’s reputation and operational efficacy. The study aims to scrutinize the moderating influence of leader mindfulness and employee moral identity on the nexus between leader surface acting and workplace incivil[1]ity, in addition to exploring the mediating role of abusive supervision within this dynamic. Thus, it is posited that both leader mindfulness and employee moral identity significantly modulate the degree to which leader surface acting is manifested as workplace incivility.